1990
DOI: 10.2307/3431032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Organophosphorus and Carbamate Insecticides

Abstract: Organophosphorus and carbamate insecticides are toxic to insects and mammals by virtue of their ability to inactivate the enzyme acetylcholinesterase. This review addresses the mechanism of inhibition of acetylcholinesterase by organophosphorus and carbamate esters, focusing on structural requirements necessary for anticholinesterase activity. The inhibition of acetylcholinesterase by these compounds is discussed in terms of reactivity and steric effects. The role of metabolic activation or degradation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
255
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(266 citation statements)
references
References 14 publications
3
255
0
8
Order By: Relevance
“…The mechanism of acute toxicity of carbamate insecticides is similar to that of OP insecticides, that is, inhibition of AChE activity at the cholinergic synapses (Fukuto 1990; Thompson and Richardson 2004). The mechanism of inhibition is similar to that proposed for hydrolysis and involves carbamylation of the nucleophilic serine, followed by release of an alcohol leaving group (Sogorb and Vilanova 2002).…”
Section: Structural and Chemical Basis Of The Carboxylesterase-carbammentioning
confidence: 99%
“…The mechanism of acute toxicity of carbamate insecticides is similar to that of OP insecticides, that is, inhibition of AChE activity at the cholinergic synapses (Fukuto 1990; Thompson and Richardson 2004). The mechanism of inhibition is similar to that proposed for hydrolysis and involves carbamylation of the nucleophilic serine, followed by release of an alcohol leaving group (Sogorb and Vilanova 2002).…”
Section: Structural and Chemical Basis Of The Carboxylesterase-carbammentioning
confidence: 99%
“…These authors suggested that mAChRs and nAChRs, as well as NMDA receptors, seem to play major roles in anticholinesterase-induced neurotoxicity and that combined treatment with cholinergic and NMDA antagonists might be beneficial in anticholinesterase-induced poisonings (Dekundy et al, 2001(Dekundy et al, , 2003. In similar studies, another NMDA receptor antagonist memantine, in combination with atropine, has been found equally effective against organophosphate and carbamate poisoning (Gupta, 1994;Gupta and Kadel, 1989, 1990, 1991a, 1991bMcLean et al, 1992).…”
Section: Effects On Neuroactivities Other Than the Cholinergic Systemmentioning
confidence: 82%
“…Inhibition occurs as a result of phosphorylation of the serine (S 200 ) included in the catalytic triad of the active center by the organophosphate (Aldridge, 1950;Fukuto, 1990). Although this inhibition is usually considered irreversible, some reactivation of phosphorylated acetylcholinesterase can occur slowly as a result of hydrolytic cleavage, if the process of aging is not complete (Sultatos, 1994(Sultatos, , 2006.…”
Section: Effects Of Organophosphates and Carbamates On Acetylcholinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of acetyl cholinesterase, acetylcholine level increased resulting in the failure of transmission of stimuli to the nerves or organs. This leads to the abnormal functioning of the body including loss of balance, moving in circular form (convulsions) and at higher concentrations of insecticides resulting in death of the organism (Fukuto 1990). Profenofos reduced the acetyl cholinesterase (Ach E) activity by 83% in the head of Eastern rainbow trout (Melanotaenia duboulayi) and 90% in the head and gills of Tilapia (Oreochromis mossambicus) (Kumar and Chapman 1998;Venkateswara et al 2003).…”
Section: Resultsmentioning
confidence: 99%